Relationship between Family Support and Motivation with Adherence to Taking Medication in the Elderly with Type 2 Diabetes Mellitus in the Working Area of UPT Puskesmas Tubaan - Marta; Andi Parellangi; Lukman Nulhakim (Formosa Journal of Multidisciplinary Research, 2023)
The percentage of deaths from diabetes in Indonesia is the second highest in the world. This study aims to determine the relationship between family support, motivation and adherence to taking medication in the elderly with type 2 Diabetes Mellitus. Using a correlational analytic design with the chi square test on 54 samples. The results of the variable values ​​of family support and medication adherence in the elderly with a p-value = 0.015, which is below α = 0.05 (p <α = 0.05) and the motivational variable with medication adherence in the elderly with a p-value = 0.665, which is above α = 0.05 (p > α = 0.05). There is a relationship between family support and adherence to taking medication in the elderly with type 2 DM.